2004
DOI: 10.1149/1.1643737
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Extracting Corrosion Parameters from the Response of the Steel-Concrete System to a Current Pulse

Abstract: The transient response to a current pulse applied to steel reinforcement bars in concrete has been analyzed by means of a new computational algorithm based on discretised approximation of the fractional difference operator. An optimization strategy has been designed to obtain a set of optimal values for the characteristic corrosion parameters from the information contained in the potential-time transient ͑specially, in the decaying part of the trace͒. The method compares the experimental response with the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 39 publications
1
41
1
Order By: Relevance
“…The elements of the equivalent circuit present the following physical meanings: R el?b is the mortar resistance, including the contribution of the electrolyte resistance; the first time constant (R pn and Q pn ) is attributed to the properties of the bulk matrix in terms of connected pore network; the second time constant (Q ct and R ct ) is normally used to evaluate charge transfer process in combination with mass transport process. When there are no mass transport limitations, R ct equals the global polarization resistance R p [35,45] and is related to the electrochemical reaction on the steel surface (widely accepted for reinforced cement-based materials is to use constant phase element (Q) instead of pure capacitance to account for steel surface, product layers, and bulk matrix heterogeneity [49,50]). …”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…The elements of the equivalent circuit present the following physical meanings: R el?b is the mortar resistance, including the contribution of the electrolyte resistance; the first time constant (R pn and Q pn ) is attributed to the properties of the bulk matrix in terms of connected pore network; the second time constant (Q ct and R ct ) is normally used to evaluate charge transfer process in combination with mass transport process. When there are no mass transport limitations, R ct equals the global polarization resistance R p [35,45] and is related to the electrochemical reaction on the steel surface (widely accepted for reinforced cement-based materials is to use constant phase element (Q) instead of pure capacitance to account for steel surface, product layers, and bulk matrix heterogeneity [49,50]). …”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…The electrochemical behavior of steel reinforcement has been extensively studied and outcomes are reported in literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The intention of this work is to see how well different electrochemical techniques agree for reinforced cement-based materials rather than obtaining absolute quantitative parameters ͑such as corrosion rate for example͒ and, further, to correlate results with structural and morphological observations of the bulk matrix and the steel/cement paste interface, thus setting up a combination of techniques for the assessment of corrosion and protection in reinforced concrete. …”
mentioning
confidence: 99%
“…Randles type circuit is useful in modelling the structure of the concrete/steel interface. This is characterised by the combined polarisation resistance (R p ) and the diffusion resistance (R D ) in parallel with a non-ideal double layer capacitance (C dl ), which is in series with the concrete (Ohmic) resistance (R O ) [8][9][10][11][12] as shown in Fig. 1.…”
Section: The Concrete-steel Interface Structurementioning
confidence: 99%
“…The corrosion properties at the concrete/steel interface can be analysed using short galvanostatic pulse method [8][9][10][11][12][13]. It has been shown that the application of a small magnitude of current pulse (<100 mC/cm 2 ) eliminates the diffusion effects in the system [8,9,14,15], allowing the system to be analysed using the equivalent electrical circuit in Fig.…”
Section: The Concrete-steel Interface Structurementioning
confidence: 99%
See 1 more Smart Citation